2016
DOI: 10.1038/onc.2016.376
|View full text |Cite
|
Sign up to set email alerts
|

TET2 binds the androgen receptor and loss is associated with prostate cancer

Abstract: Genetic alterations associated with prostate cancer (PCa) may be identified by sequencing metastatic tumor genomes to identify molecular markers at this lethal stage of disease. Previously, we characterized somatic alterations in metastatic tumors in the methylcytosine dioxygenase ten-eleven translocation 2 (TET2), which is altered in 5–15% of myeloid, kidney, colon and prostate cancers. Genome-wide association studies previously identified non-coding risk variants associated with PCa and melanoma. We performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 54 publications
1
43
0
1
Order By: Relevance
“…In addition to melanoma, TET2 has been shown to be down-regulated in an androgendependent manner in prostate cancer, with lower expression conferring worse prognosis for patients (Nickerson et al 2016). In colorectal cancer, TET2 has been shown to be excluded from the nucleus , with similar findings for TET1 in glioma (Waha et al 2012).…”
Section: Other Diseasesmentioning
confidence: 98%
“…In addition to melanoma, TET2 has been shown to be down-regulated in an androgendependent manner in prostate cancer, with lower expression conferring worse prognosis for patients (Nickerson et al 2016). In colorectal cancer, TET2 has been shown to be excluded from the nucleus , with similar findings for TET1 in glioma (Waha et al 2012).…”
Section: Other Diseasesmentioning
confidence: 98%
“…Interestingly, TGF-β was shown to regulate the expression of DNMTs in prostate cancer, with their expression correlating with aggressiveness and recurrence (Zhang et al 2011b). Both TET1 and TET2 were shown to play a tumor-suppressive role in prostate cancer through regulation of cell proliferation, migration, and invasion (Hsu et al 2012;Nickerson et al 2017).…”
Section: Epigenetic Deregulationmentioning
confidence: 99%
“…Five‐methylcytosine (5mC) is a regulator of DNA methylation, which is a process crucial to tumorigenesis; in addition, 5mC can be switched into 5‐hydroxymethylcytosine (5hmC) by the activations of ten‐eleven translocation (TET) family, including TET2 . Previous studies have revealed the roles of 5mC, 5hmC, and TET2 in multiple cancers, including regulating cancer progression and serving as diagnostic or prognostic biomarkers in clinical practice . More importantly, there are reports illuminating that 5mC, 5hmC, and TET2 also participate in breast cancer etiology, including the regulation of tumor suppressor genes and DNA methylation .…”
Section: Introductionmentioning
confidence: 99%